Bioavalaibility and pharmacokinetic comparison of two formulations of metformin 850 mg tablets in healthy Colombian volunteers (Colombia Medica, 2024)
urpose: The aim of this study was to compare the bioavailability of two formulations of metformin 850 mg tablets: Glucophage® from Merck Santè laboratories (reference product) and Metformin from Winthrop Pharmaceuticals de Colombia SA (test product) in healthy Colombian volunteers. Methods: A random, double blind, two-period, two-week wash out period, crossover study was performed in 24 healthy male and female volunteers for a single 850-mg dose of metformin tablets administrated with 240 ml of water after 12 hours of fasting. Once the drug was administrated, blood samples were collected before and within 24 hour, and plasma metformin concentration was determined by using a validated HPLC method. Pharmacokinetic parameters such as Cmax, AUC0-96h, AUC0-∞, and Tmax were determined. The formulations were considered bioequivalent if the logarithmic mean ratios of ln-transformed Cmax and AUC0-∞ values were within the equivalence range of 80%-125%. Results: ANOVA analysis of the ln-transformed Cmax and AUC0-∞ indicated that none of the effects examined (formulation, period, within and between-subjet variances and carry over) was statistically significant. The mean (±SD) of Cmax 1217.38 (± 251.72) ng/ml vs. 1305.25 (± 301.06) ng/ml, AUC0-96h 1363.49 (± 315.51) ng.h/ml vs. 1584.82 (± 368.75) ng.h/ml, AUC0-∞, 7155.75 (± 1440.74) ng.h/ml vs. 7777.08 (± 1896.49) ng.h/ml, and Tmax 2.57 (± 0.93) h vs. 2.22 (± 0.94) h were obtained with test and reference formulations, respectively. These pharmacokinetic parameters presented differences with the results from other published papers. The 90% confidence interval of the logarithmic ratio of AUC0-∞ and Cmax was within the range of 80-125%. Conclusions: In this study in healthy Colombian volunteers, a single 850-mg dose of metformin tablet test formulation met the criteria for bioequivalence to the reference formulation based on pharmacokinetic parameters AUC0-∞ and Cmax.